1996
DOI: 10.1002/(sici)1097-0142(19960215)77:4<733::aid-cncr20>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Randomized trial of initial therapy with melphalan versus cisplatin-based combination chemotherapy in patients with advanced ovarian carcinoma: Initial and long term results—Eastern Cooperative Oncology Group study E2878

Abstract: In women with advanced ovarian cancer, initial therapy with a cisplatin-based combination chemotherapy regimen resulted in higher clinical complete response rates and longer time to failure compared with initial therapy with a single, oral alkylating agent; however, the benefits of this approach were confined to women older than 50 years of age at diagnosis, and there was no significant difference in survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Results from multiple early trials suggested that regimens that included a platinum agent resulted in better response rates and PFS (compared with other chemotherapy options). 197,198 Subsequent trials aimed at determining which platinum-based combinations are the most effective and safe.…”
Section: Options For Intravenous Chemotherapymentioning
confidence: 99%
“…Results from multiple early trials suggested that regimens that included a platinum agent resulted in better response rates and PFS (compared with other chemotherapy options). 197,198 Subsequent trials aimed at determining which platinum-based combinations are the most effective and safe.…”
Section: Options For Intravenous Chemotherapymentioning
confidence: 99%
“…Across studies, median progression-free survival was about six months and median overall survival was about 12 months. After 10 years of follow-up, 95% of patients had progressed and 90% of patients had died [8,9].…”
Section: Trends In Case-fatalitymentioning
confidence: 99%
“…The introduction of platinum was widely viewed as the turning point of ovarian cancer treatment. However, long-term results revealed that after ten years, 90% of patients had developed recurrent disease (versus 95% of patients before cisplatin) and 85% of patients had died (versus 90% before cisplatin) [8]. In SEER, from 1978 to 1984 (following the introduction and expansion in use of cis-platinum), five-year case-fatality rates of advanced ovarian cancer fell by about 6% and 12-year case-fatality fell by only 3.5%.…”
Section: Trends In Case-fatalitymentioning
confidence: 99%